Gender, Islam dan Hak Asasi Manusia - Abd. Azis (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2003)
The new problem but last is the misinterpretation of gender, which is caused by social constructions, law, politic and religion. Its cause one of sexes, recently called gender, marginalized and subordinated. Women and men were not placed as human being who have the same opportunities and equalities in the public roles, law, education, and religion. All of the causes we called bias gender in whole our life, so that we must take forward in reinterpretation of it. Our God never treats the differences His prayers, the differentiation between women and men is only based on roles each others and quality of faith. Subordination, marginalization, molestation and discrimination are broken of human rights itself and religion.